Endoscopic Endonasal Transclival Approach to Ventral Pontine Cavernous Malformation: Case Report - Dong, Xiao; Wang, Xiaoyu; Shao, Anwen; Zhang, Jianmin; Hong, Yuan (Frontiers in Surgery, 2021)
Ventral medial pontine cavernous malformations are challenging due to the location in eloquent tissue, surrounding critical anatomy and potential symptomatic bleeding. Conventional approaches, such as anterolateral, lateral and dorsal approach, are associated with high risk of deleterious consequences due to excessive traction and damage to the surrounding tissues. The authors present an endoscopic endonasal approach for the resection of midline ventral pontine cavernous malformations, which follows principles of optimal access to brainstem cavernous malformations as the “two-point method”. No CSF leak or any other complications are obtained. The successful outcomes indicate that an individualized approach should be chosen before the surgery for brainstem cavernous malformations. With the advance of techniques, endoscopic endonasal approach could provide the most direct route to ventral pontine lesions with safety and efficiency.